Implementasi Pendidikan Akhlak untuk Meningkatkan Karakter Religius Siswa Sdit Darul Abidin Depok - Tarjudi, Tarjudi (Universitas Syiah Kuala, 2025)
Character education (morals) is a structured process that aims to shape noble character through tazkiyatun nafs (purification of the soul) and the cultivation of good habits, based on the Qur'an and Hadith. This study aims to: (1) explore how existing challenges can be overcome through good communication, (2) optimal utilization of resources, (3) supportive attitudes of implementers, and (4) a bureaucratic structure that supports the achievement of Islamic education goals.A qualitative case study approach was used, with data collected through in-depth interviews, direct observation, and document analysis. The data was processed in three stagescondensation, display, and drawing conclusionswhile credibility was ensured through triangulation.Findings indicate that SDIT Darul Abidin structures moral education into three domains. First, morality towards God, instilled through activities such as daily prayers, Dhuha prayer, Quran recitation and memorization, congregational prayers, voluntary fasting, and Quran completion. Second, morality towards others, developed through practices like handshakes with teachers, participation in Islamic Personality Development (BPI), commemorating Islamic events, performing qurban, and distributing takjil. Third, morality towards the environment, encouraged through waste sorting, minimizing plastic use, and conserving water.Implementation proceeds in three stages: (a) planning, which involves defining character standards, designing activities, and preparing facilities; (b) execution, which integrates values into learning, reinforces habits, emphasizes teacher role modeling, and promotes a religious school culture; and (c) evaluation, which uses attendance records, reflection, and rubric-based assessments.Overall, moral education at SDIT Darul Abidin is successfully implemented, as reflected in the effective execution of activities and the notable enhancement of students religious character.